Biochemical pH Buffer Standards of the Zwitterionic Buffer TES (N-Tris-(Hydroxymethyl) Methyl- 2-Aminoethanesulfonic Acid) from \(5^°\)C to \(55^°\)C - Rabindra N. Roy; Lakshmi N. Roy; Blake M. Bodendorfer; Zachary M. Downs; Stephen D. Rocchio; Joshua T. Wollen; Jessica M. Stegner; Isaac B. Henson; Nicholas W. Grove; Lauren A. Dieterman (Science and Technology: Developments and Applications Vol. 5, 2025)
A selected group of zwitterionic buffers has been proposed for physiological use. The authors have undertaken the determination of pH values for one buffer solution of TES without NaCl and nine buffer solutions with NaCl yielding an ionic strength I = 0.16 mol \(·\) kg-1 similar to that of blood. The TES was obtained from Research Organics in Cleveland, OH. The experimental method for further crystallization and the assay have been previously reported in detail. These buffer solutions have been evaluated in the temperature range of \(5^°\)C to \(55^°\)C using an extended version of the Debye-Hückel equation. The pH values are reported using 1) the Debye-Hückel extension of the Bates-Guggenheim convention in the temperature range \(5^°\)C to \(55^°\)C and 2) with and without liquid junction correction at \(25^°\)C and \(37^°\)C . These TES buffer solutions are recommended as secondary standard references for pH measurements in the range of pH 7.2 to 7.5 for physiological applications with an ionic strength of I = 0.16 mol \(·\) kg-1 .